Seizure: Virals Series #2 - Reichs, Kathy (New York : Razorbill, 2011)
Tory Brennan and her Virals friends work to prevent the financially strapped Loggerhead Island Research Institute's imminent shutdown, an effort that leads them to investigate an old Charleston buried treasure legend.
Sequel to: Virals.
Keywords: Buried treasure -- Fiction; Virus diseases -- Fiction; Fathers and daughters -- Fiction; Adventure and adventurers -- Fiction; Buried treasure -- Fiction; Viruses -- Fiction; Father-daughter relationship -- Fiction; South Carolina -- Fiction; South Carolina -- Fiction; Adventure fiction; Science fiction